Acute Graft-vs.-Host Disease-Associated Endothelial Activation in vitro Is Prevented by Defibrotide - Martinez-Sanchez, Julia; Hamelmann, Hannah; Palomo, Marta; Mir, Enrique; Moreno-Castaño, Ana Belen; Torramade, Sergi; Rovira, Montserrat; Escolar, Ginés; Cordes, Steffen; Kalupa, Martina; Mertlitz, Sarah; Riesner, Katarina; et al. (Frontiers in Immunology, 2019)
Angiogenesis and endothelial activation and dysfunction have been associated with acute graft-versus-host disease (aGVHD), pointing to the endothelium as a potential target for pharmacological intervention. Defibrotide (DF) is a drug with an endothelium-protective effect that has been approved for the treatment of veno-occlusive disease/sinusoidal obstruction syndrome after allogeneic hematopoietic cell transplantation. Clinical data suggest that DF also reduces the incidence of aGVHD; however, the mechanisms of DF-mediated aGVHD regulation have not been examined. To investigate possible DF-mediated prophylactic and therapeutic mechanisms in aGVHD, we performed in vitro studies using endothelial cell (EC) lines. We found that DF significantly and dose-dependently suppressed EC proliferation, and notably reduced their ability to form vascular tubes in Matrigel. To explore whether DF administered prophylactically or therapeutically has a significant effect on aGVHD endothelial dysfunction, ECs were exposed to media containing sera from patients with aGVHD (n = 22) in the absence or presence of DF, and from patients that did not develop aGVHD (n = 13). ECs upregulated adhesion molecules (VCAM-1, ICAM-1), the adherence junction protein VE-cadherin, von Willebrand factor, and Akt phosphorylation in response to aGVHD sera. These responses were suppressed upon treatment with DF. In summary, DF inhibits vascular angiogenesis and endothelial activation induced by sera from aGVHD patients. Our results support the view that DF has notable positive effects on endothelial biology during aGVHD.